Biomarkers in head and neck squamous cell carcinoma: unraveling the path to precision immunotherapy - Saini, Kamal S.; Somara, Sasikala; Ko, Heidi C.; Thatai, Purva; Quintana, Angela; Wallen, Zachary D.; Green, Michelle F.; Mehrotra, Ravi; McGuigan, Sandra; Pang, Lingjuan; Das, Soma; Yadav, Kavita; et al. (Frontiers in Oncology, 2024)
Recent strides in understanding the molecular underpinnings of head and neck cancers have sparked considerable interest in identifying precise biomarkers that can enhance prognostication and enable personalized treatment strategies. Immunotherapy has particularly revolutionized the therapeutic landscape for head and neck squamous cell carcinoma, offering new avenues for treatment. This review comprehensively examines the application and limitations of the established and emerging/novel biomarkers for head and neck squamous cell carcinoma. Established biomarkers, including well-characterized genetic mutations, protein expressions, and clinical factors, have been extensively studied and validated in clinical practice. Novel biomarkers identified through molecular analyses, including novel genetic alterations, immune-related markers, and molecular signatures, are currently being investigated and validated in preclinical and clinical settings. Biomarkers hold the potential to deepen our understanding of head and neck squamous cell carcinoma biology and guide therapeutic strategies. The evolving paradigm of predictive biomarkers facilitates the study of individual responses to specific treatments, including targeted therapy and immunotherapy.